Hurdles in starting laparoscopy in a rural medical college: our experience - Sangwan, Vijayata; Sangwan, Mukesh; Siwach, Sunita; Lakra, Pinky; Mahendroo, Rajiv; Kansal, Richa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Although laparoscopy surgery has certain proved advantages over open surgery like less scarring, less postoperative pain, early return to work etc. but has a long learning curve. The pressure of feeling we are behind as a surgeon if we don’t embrace laparoscopy made us to take it on. With this paper we want to share our experiences i.e. beginner problem we faced, efforts and modification we adopted and current status of our journey. The aim of the study was to highlight the difficulties in starting laparoscopic surgeries and how to overcome them. Methods: This is a retrospective study of all laparoscopic procedures performed in our newly established government medical college in rural India was started from 2013. Results: We have performed cases of 27 diagnostic laparoscopy, 10 cases of laparoscopic ovarian cystectomy, 09 cases of ectopic pregnancy and cases of LAVH and 05 cases of TLH. Over a period of about two years out of total only 8 cases were performed in first year of study. It was our technical deficiency, nonavailability of mentor, anesthetists’ reluctance for general anaesthesia due to prolonged duration of surgery and administrative pressure of long waiting list. To overcome these problems we underwent lap training with experts, attended CMEs, conferences and convinced anesthetists and administration for these surgeries. We also selected and trained our O.T. staff about technical demands of laparoscopy. Conclusions: Start by doing what is necessary; then do whats possible and suddenly you are doing impossible. However conversion to open surgery should be kept at low threshold rather than landing yourself and patient in complications.